FACILITIES DEVELOPMENT OF FACILITIES AND INFRASTRUCTURE IN THE FORM OF LIGHTING, SERVICES, AND IMPROVEMENTS AT SERAYA BEACH, BALIKPAPAN SELATAN DISTRICT, RT. 28 - Vicky Andria Kusuma; Maulana Rahmatullah; Aldila Putra; Dicky Ocza; Reza Faiz; Setya Dwi; Yashinta Putri; Miftahul Janna; Rahayu Ridha (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
The Student Engagement in Village Development Program (PMMD) stands as a significant initiative undertaken at the Kalimantan Institute of Technology, with a keen focus on the development of Pantai Seraya. Situated on Sepinggan Raya I Street, RT 28, Sepinggan Subdistrict, South Balikpapan District, Balikpapan City, East Kalimantan, Pantai Seraya embodies a captivating potential for natural tourism that appeals to the residents of Balikpapan. However, this promising potential is hindered by the lack of necessary facilities and infrastructure to deliver a satisfying tourist experience. The lack of visitor interest stems from this very condition. In this context, we strongly propose an urgent solution involving the construction of essential facilities, including seating arrangements, illumination, and waste disposal units at Pantai Seraya. The primary objective is to elevate the comfort of visitors. Nevertheless, sustainability also takes center stage in this development. With an expected increase in visits over time, preserving the cleanliness of the beach and its surroundings becomes paramount. This action will not only ensure a positive tourism experience but will also safeguard the coastal ecosystem for the long term. Consequently, Pantai Seraya is envisioned to emerge as a premier destination in Balikpapan, offering both economic and ecological benefits, creating livelihood opportunities for the local community, and fostering awareness regarding the necessity of maintaining beach cleanliness among tourists and local residents.